SENI TEREBANG PADA UPACARA RUWATAN RUMAH DI DESA KARANG TUNGGAL KECAMATAN PASEH KABUPATEN BANDUNG - Adang Kusnara (SURYA SENI, 2007)
The blessings of a house, also called ‘Ruwatan rumah’ is a sacred ceremony which is still being celebrated by those who believed in it. The people of Karang Tunggal still do such ceremony today. There is an important aspect which wastried to be brought up in this celebration. The aspect is the effort to preserve the cultural values in heritaged by the ancestors. The blessing of a house gives chances to other arts to develop, such  ‘terebang’ a kind of tradisional art, therefore such art can take part on the ceremony. The ceremony itself producer lots different values and is nothing than just an ordinary ceremony. There are social, economical, entertaiment, aesthetical, cultural and educational  values in the ceremony.These values arise because there are different kinds of  erceptions from different kinds of people, and also dependson where the ceremony is being held. Terebang in Karang Tunggal in the beginning was a medium to teach Moslem, today the art itself is used as a requirement on celebrating the ceremony and also as a kind of entertainment for the people Terebangan involves  dancing, which is a very important aspect of the ceremony, because if the dancing areeliminated the ceremony will not be complete. Therefore, for the people of Karang Tunggal terebang functions as :(1) a medium to celebrate the ceremony,  it is mainly because this kind of art one of the requirements to accompany theceremony, especially the blessing of a house done by the people of Karang Tunggal.(2) a kind of entertaiment. Terebang is performed to the public to entertaint them. Terebangis also held during special ceremonies such as the circumcisionof a boy in wedding parties.    Keywords: Terebang and Ruwatan rumah